PENGEMBANGAN KARAKTER MELALUI BENDERA PRESTASI (Studi Kasus di Kelas 4 Ahmad Dahlan SDIT Salsabila 2 Klaseman) - Ahmad Safi’i (QURROTI, 2019)
Society is increasingly aware of the importance of character education. In celebrating National Teacher's Day 2017, character education and exemplary teachers are also the main theme. However, the emphasis on the importance of character education is sometimes not evenly applied by teachers in the teaching and learning process. The research method used is descriptive qualitative with field research. The research subjects were the 4th grade students of Ahmad Dahlan at SDIT Salsabila 2 Klaseman, teachers, principals and guardians of students. The results showed that the cause of the weak character in the class was the teacher's concentration which was too focused on developing students' academic potential and not touching their character. The strategy applied to overcome this problem is the Achievement Flag. The implementation steps are: (1) Giving one free flag to all children as bait, (2) Giving flags to those who do good regardless of the type, (3) Every Friday the flags are accumulated the most, (4) Mondays are announced when apples or ceremonies flags, (5) Given an award certificate as Student of The Week and won a door prize, (6) Photos of outstanding children displayed in front of the classroom door, (7) Successfully collecting 10 certificates will get a super door prize, (8) Maintain program intensity, and ( 9) Packaged like a game (game). High children's interest in competing to do good with their friends. The supporting factor for the program is support from the school principal, student guardians, and other teachers. The inhibiting factor is miscommunication that occurs because of the slow response between teachers and parents.